The American Deists Voices of Reason and Dissent in the Early Republic - Walters, Kerry S. (University Press of Kansas, 1992)
Challenging carvedinstone tenets of Christianity, deism began sprouting in colonial America in the early eighteenth century, was flourishing nicely by the American Revolution, and for all intents and purposes was dead by 1811. Despite its hasty demise, deism left a theological legacy. Christian sensibility would never be quite the same.Bringing together the works of six major American deists-Benjamin Franklin, Thomas Jefferson, Ethan Allen, Thomas Paine, Elihu Palmer, and Philip Frenau-an dthe Frechman Comte de Volney, whose writings greatly influenced the American deists, Kerry Walters has created the fullest analysis yet of deism and rational religion in colonial and early America. In addition to presenting a chronological collection of several works by each author, he provides a description of deism's historical roots, its major themes, its social and political implications, and the reasons for its eventual demise as a movement.Essential readings from the three major deistic periodicals of the period-Temple of Reason, Prospect, and the Theophilanthropist-also are included in the volume. This is the first time they have been reprinted since their original publication.American deism is more than merely an antiquated philosophical position possessing only historical interest, Walters contends. Its search for a religion based upon the ideals of reason, nature, and humanitarianism, rather than the blind faith, scriptural inerrancy, and miracles preached by Christian churches at the time, continues to offer insight of real significance.